2004
DOI: 10.2166/wst.2004.0321
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of bisphenol A (BPA), 4-nonylphenol (4-NP) and 4-nonylphenol ethoxylates (4-NP1EO, 4-NP2EO) in oxidative water treatment processes

Abstract: Endocrine disrupting chemicals (EDCs) such as natural and synthetic hormones or industrial chemicals can adversely affect the endocrine system at very low concentrations. As such substances can be present in raw water used for drinking-water production, they potentially pose a health risk to humans. In this study laboratory tests were performed to determine removal efficiencies of selected oxidative drinking water treatment processes, namely ozonation (1.4 mg/l O3) and chlorination, using sodium hypochlorite (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 9 publications
2
14
1
1
Order By: Relevance
“…Lenz et al (2004) found that in a solution containing 1.4 mg l À1 ozone, the concentration of 4-NP (C 0 ¼ 1-200 mg l À1 ) could be reduced to less than 20 ng l À1 within 5 min and the estrogenic activity to less than 95% of the original. A similar study by Kim et al (2005) showed that despite the rapid breakdown of 4-NP by 1 h ozonation, the concentration of dissolved organic carbon remained constant throughout.…”
Section: Dark Advanced Oxidation Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lenz et al (2004) found that in a solution containing 1.4 mg l À1 ozone, the concentration of 4-NP (C 0 ¼ 1-200 mg l À1 ) could be reduced to less than 20 ng l À1 within 5 min and the estrogenic activity to less than 95% of the original. A similar study by Kim et al (2005) showed that despite the rapid breakdown of 4-NP by 1 h ozonation, the concentration of dissolved organic carbon remained constant throughout.…”
Section: Dark Advanced Oxidation Reactionsmentioning
confidence: 99%
“…They found that 99% of BPA was converted with an initial ozone concentration of 30 mM in less than 2 s. However, the level of estrogenicity increased during initial contact, declined after subsequent contact and stabilized after 60 min, signifying that the oxidation byproducts had higher estrogenic activity than BPA and some residual estrogenic response remains after treatment. Behavior of BPA in oxidative water treatment facilities was also studied by Lenz et al (2004), who reported 1.4 mg l À1 as the optimum O 3 concentration for complete BPA destruction and 5 min as the sufficient contact time for removing the endocrine activity without the formation of adsorbable organic halogens.…”
Section: Dark Advanced Oxidation Reactions With Ozone Ultrasound Andmentioning
confidence: 99%
“…Likewise, further research is needed to determine the effect of oxygen on sorption/ desorption equilibrium. Finally, this procedure has demonstrated to be environmentally friendly because it avoids the application of a tertiary oxidative treatment that usually causes secondary pollution (Lenz et al 2004). Moreover, the economical balance is positive despite the higher cost of pure oxygen because the use of oxygen also reduces sludge production, which means lower operating time and lower electricity consumption.…”
Section: Effect Of Application Of Pure Oxygen Into the Bioreactormentioning
confidence: 99%
“…In this respect, several studies have focused on the application of tertiary treatments, which usually include an oxidative process. These treatments are usually effective (Lenz et al 2004;Schröder 2006) but they may result in high expenses and secondary pollution, caused by the presence of residual amounts of the oxidants or their byproducts in water.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, removal of aqueous NPs by electrochemical [8], ozonation [8][9][10][11][12], photolysis with UV [13], Photocatalysis with UV/TiO 2 and UV/BiVO 4 [12,[14][15][16], and Sonolysis with Fe(II) and Fe(III) [17] has been reported.…”
Section: Introductionmentioning
confidence: 99%